Management of Hydrallantois in a Cow by Transabdominal Allantocentesis - Shreemathi, Ravi; Gopikrishnan, Duraisamy; Gopal, Kuppusamy; Palanisamy, Mahakrishnan (The Indian Journal of Animal Reproduction, 2026)
The present report describes a case of hydrallantois in a three-year-old primiparous Jersey crossbred cow and its suc cessful clinical management. The animal exhibited sudden bilateral abdominal distension, respiratory distress, anorexia, and difficulty in locomotion. Per-rectal examination revealed a tense, fluid-filled uterus with non-palpable fetal parts. Parturition was induced using prostaglandin and dexamethasone; however, due to inadequate cervical dilation, transab dominal allantocentesis was performed to gradually drain approximately 50 litres of allantoic fluid. Subsequently, a dead female fetus was delivered with mild traction. Histopathological examination of the fetal kidney revealed cystic dilatation and cortical atrophy. The dam recovered uneventfully following supportive therapy. Controlled drainage of allantoic fluid through transabdominal allantocentesis proved to be an effective and life-saving management approach.
Keywords: Allantocentesis; Cow; Hydrallantois; Fetal dropsy